A social survey of the educational institutions for Africans in Cape Town - Giugni, Giovanni L (Department of Social Development, 2016)
The specific aim of the survey was twofold, first to find out what educational institutions are "available" in Cape Town for Africans (whether they are numerically adequate, are sufficiently well suited and equipped, and are strategically located in proximity to pupils' homes; and how the social circumstances or the pupils and of the staffs affect school training); second; to find out to what extent the existing schools are "utilized'' by the Africans. In addition, the survey also considers the broader question of school education for Africans, which has become at present one of the major problems of the whole country together with the social and political re-organization of the Bantu community. To re-organize socially is first of all to re-organize mentally, a task which is proper of education in general and of school education in particular.